An Assessment on Current Knowledge and Adoption of Napier Fodder for Enhancing Milk Production in Smallholder Dairy Farms in Kandawalai Veterinary Surgeons Division - Kajaranjan, S.; Sasiharan, R.; Kirijakala, S. (University of Jaffna, 2025)
Our country heavily relies on importing milk and milk products, which account for 58% of national consumption, to bridge the gap between supply and demand. Consequently, there is an urgent need to increase local milk production. A holistic approach to improving milk production involves improving both the quality and quantity of cattle feed. This can be achieved by promoting the cultivation of Napier fodder for cattle feeding. This study aimed to assess the knowledge, awareness, and adoption of Napier fodder among smallholder dairy farmers in the Kandawalai Veterinary Division. The study investigates the impact of Napier fodder on milk production, identifies key factors affecting its adoption, and proposes recommendations to overcome existing barriers. Data were collected through structured questionnaires from 125 randomly selected dairy farmers. The responses were analysed by thematic categories and processed in Microsoft Excel. The research findings reveal that 67% of Napier fodder cultivators are male, and 81% of farmers maintain herds of one to five milking cows. Although 85% of farmers are aware of Napier's benefits, only 4% dairy farmers cultivate and feed it daily. Intensive management systems with Napier feeding result in higher average milk production (6.8 liters/cow/day) and better body condition scores (2.5 to 3.0 BCS), and disease incidence below 2%. Conversely, semi intensive systems without Napier feeding show lower productivity and higher disease rates. Key constraints include limited resources for fodder cultivation (42%) and inadequate technical knowledge (15%), with 64% of farmers expressing a need for financial support to cultivate Napier fodder. The low adoption rate underscores the need for targeted technical training, improved access to resources, and government subsidies to enhance Napier fodder production for dairy productivity.
Keywords: Cattle farming; Fodder; Milk production; Napier